People's wellbeing, civic capital and sustainable practices: Evidence from the European Values Study survey - Ciziceno, Marco (Frontiers in Sociology, 2023)
The climate change issue is showing an unprecedented level of awareness in the political realm. Changing occasional sustainable practices into stable behaviors is the challenge that policymakers face. However, what makes people environmentally aware is an unsolved question, and research on this direction is in evolution. This paper examines factors that promote environmentally responsible behaviors. The study tests the hypothesis that people's wellbeing (SWB) predisposes individuals toward environmentalism. The mechanism of social and civic capital may underlie this association since people reporting higher wellbeing levels show empathy, solidarity, and greater civic engagement. This hypothesis is examined in the context of the European Union using micro-data from the European Values Study—EVS (wave 2017–2022). Results support the hypothesis that people's life satisfaction is compatible with the environmental mindset, given that those who report higher wellbeing express civicness and share pro-environmental beliefs and values. Evidence from this research suggests that supporting SWB growth may offer a fertile ground for promoting ecological awareness and developing more sustainable societies.